PENGARUH FRAUD PENTAGON THEORY DAN FAKTOR LAINNYA YANG MEWAKILI TERHADAP KECURANGAN LAPORAN KEUANGAN - Debora, Debora; Tandy, Jessica Amanda (E-Jurnal Akuntansi TSM, 2024)
This research aims to obtain empirical evidence of the influence of factors that can affect fraudulent financial reporting using fraud pentagon. The independent variables used in this research consisting external pressure, effective monitoring, rationalization, capability, arrogance, financial targets, financial stability, and nature of industry. The population of this research are consumer cyclicals dan non-cyclicals listed on the IDX (Indonesia Stock Exchange) during 2020-2022. The sample of this research is selected by using purposive sampling, so that the sample obtained is 177 samples. The data collection method is the quantitative method using secondary data. The analysis technique used is logistic regression analysis with SPSS Version 25.0. The results show that external pressure, effective monitoring, rationalization, and arrogance has an effect on the probability of fraudulent financial reporting. In contrast, capability, financial targets, financial stability, and nature of industry have no impact on fraudulent financial reporting.